Assessing natural resource internships: A social cognitive analysis of national diversity programs. Issue 2 (3rd April 2019) - Morales, Nia; Jacobson, Susan K.
ABSTRACT: We assessed influences of conservation and natural resource (CNR) internships on minority students' perceptions of self-efficacy and CNR career goals and expectations, based on social cognitive career theory. We conducted six focus groups using Q methodology, surveyed 134 students, and followed up with 23 alumni and a control group of 11 candidates one year later to measure the impacts of three national programs. Results showed significant increases in knowledge, more positive perceptions and outcome expectations, higher self-efficacy, and increased interest in CNR careers. After one year, alumni continued reporting positive changes and greater perceptions of competitiveness for CNR careers than the control group despite both groups having similar rates of volunteerism/job history in CNR. Results also suggest the need to involve students earlier to encourage interest in CNR careers.